A Modification Technique of Collision Probability in the Direct Simulation Monte Carlo Method. (2015) - Fei, Huang; Pengfei, Li; Xu-hong, Jin; Xiaowen, Liu; Xiaoli, Cheng
Abstract: In Direct Simulation Monte Carlo (DSMC) method, it is difficulty to keep grid size smaller than local mean free path, that influences calculation accuracy much. In this paper, a new modification technique of collision probability with least square method and sub-relaxation technique is introduced to improve simulation accuracy in DSMC with coarse grid size. The new method is applied to direct simulation Monte Carlo method based on unstructured tetrahedral cells, which can be easily used for other grid topology. A numerical example with different grid size is implemented to validate the method discussed here, and the numerical results confirm feasibility of the modification technique.